Contribution to the analysis of plant pathogen resistance genes - (:unkn) unknown (My University, 2024)
My research focuses on the analysis of the genetic bases of plant resistance, particularly cereals, to pathogens. During a postdoctoral fellowship at the University of Zurich, I participated in the positional cloning of the Lr10 gene involved in the wheat/Puccinia triticina interaction. The rest of my activities focused on the rice/RYMV (rice yellow mottle virus) interaction, a major pathogen of rice cultivation on the African continent. I developed approaches in genetics, genomics and, more recently, functional analysis. I contributed to (i) the identification of sources of varietal resistance, three major genes and resistance QTLs and their characterization, (ii) the analysis of the risks of circumvention of resistance genes and the understanding of the molecular bases of this circumvention (iii) the development of resources (plant material and molecular markers) usable for varietal improvement. More punctually, I also participated in work on the genetic and genomic characterization of cultivated rice.The research project that I propose to develop in the coming years concerns the characterization of the tripartite interactions rice/Polymyxa graminis/RSNV (rice stripe necrosis virus). RSNV is a virus transmitted to rice by P. graminis (a soil protist that is a root parasite) and which causes increasing damage in South America and is re-emerging in Africa. The objective of the project is to (i) develop tools to facilitate the study of this pathosystem which is still very poorly understood, (ii) characterize the infectious process and the specificities of infection on susceptible hosts depending on the diversity of the virus and the vector, (iii) identify sources of resistance in cultivated rice and their wild relatives and characterize the genetic factors responsible for resistance.
Keywords: African Research